On Code-Phagocytosis Writing in El Diario (1606) by Domingo Chimalpáhin - Viveros, Alejandro (Meridional. Revista Chilena de Estudios Latinoamericanos, 2017)
This paper considers a concept called “Code-Phagocytosis Writing” as a platform to analyze and interpret Domingo Chimalpáhin’s Diario (1606). With this in mind we will question where the chronicles and writings of colonial Indians fit within their historical-literary work. We will discuss the construction of cultural texts and translations generally classified under the historical-literary genre of the chronicle. Based mainly on the ideas presented by Bolívar Echeverría with respect to literature, historiography, and philosophy, we will explain what we understand by “code-phagocytosis writing”. Then, through Chimalpáhin’s work and using the solar eclipse of June 10th of 1611 as an example, we will analyze his use of “Code-Phagocytosis Writing” through his questions and expressions.